2022
DOI: 10.5090/jcs.22.085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes after Upfront Surgery in Clinical Stage I–IIA Small Cell Lung Cancer

Abstract: Background: Upfront surgery followed by systemic treatment is recommended to treat clinical stage I-IIA small cell lung cancer (SCLC), but data on the clinical outcomes are sparse. Thus, this study evaluated the stage migration and long-term prognosis of surgically treated clinical stage I-IIA SCLC. Methods: We retrospectively reviewed 49 patients with clinical stage I-IIA SCLC who underwent upfront surgery between 2000 and 2020. Additionally, we re-evaluated the TNM (tumor-node-metastasis) staging according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…A recent study demonstrated favorable surgical outcomes in a large cohort of patients with small cell lung cancer [12]. Additionally, Woo et al [13] reported promising survival results following upfront surgery for patients with this form of cancer. Upfront surgery may offer benefits in the early stages of tumors with high mitotic activity, such as small cell lung cancer.…”
Section: Jcsmentioning
confidence: 99%
“…A recent study demonstrated favorable surgical outcomes in a large cohort of patients with small cell lung cancer [12]. Additionally, Woo et al [13] reported promising survival results following upfront surgery for patients with this form of cancer. Upfront surgery may offer benefits in the early stages of tumors with high mitotic activity, such as small cell lung cancer.…”
Section: Jcsmentioning
confidence: 99%